The Impact of Materiality: Accounting's Best Kept Secret - Niamh Brennan; Sidney J. Gray (Asian Academy of Management Journal of Accounting and Finance, 2005)
This paper comprises a review of the literature on materiality in accounting. The paper starts by examining the context in which materiality is relevant, and the problems arising from applying the concept in practice. Definitions of materiality from legal, accounting and stock exchange sources are compared. The relevance of materiality to various accounting situations is discussed. Methods of calculating quantitative thresholds are described and illustrated. Prior research is reviewed, focussing on materiality thresholds, and on the materiality judgments of auditors, preparers and financial statement users. The paper concludes with some suggestions for future research and for policy makers concerning this best kept accounting secret.